-2(2s-4)-8=-2(5s+8)-3

Simple and best practice solution for -2(2s-4)-8=-2(5s+8)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2s-4)-8=-2(5s+8)-3 equation:



-2(2s-4)-8=-2(5s+8)-3
We move all terms to the left:
-2(2s-4)-8-(-2(5s+8)-3)=0
We multiply parentheses
-4s-(-2(5s+8)-3)+8-8=0
We calculate terms in parentheses: -(-2(5s+8)-3), so:
-2(5s+8)-3
We multiply parentheses
-10s-16-3
We add all the numbers together, and all the variables
-10s-19
Back to the equation:
-(-10s-19)
We add all the numbers together, and all the variables
-4s-(-10s-19)=0
We get rid of parentheses
-4s+10s+19=0
We add all the numbers together, and all the variables
6s+19=0
We move all terms containing s to the left, all other terms to the right
6s=-19
s=-19/6
s=-3+1/6

See similar equations:

| -5x-5=-29 | | 20.92=4g+3.68 | | 368=-16v | | X=10x+21 | | 4(2x+8)=-34+10 | | -7/3=2/7v-5/2 | | 12x+12x=36 | | 3(2x+5)=-15+24 | | 300+10=900t | | 4-x=-x+1 | | 4(2×-3)=5x-42-2x | | 6y+12=−3y−6 | | -2x+-2+3x=14 | | 11r=-55 | | 7k+20=13k+28 | | –6(p–8)=–12 | | 6v+4-3(-6v-2)=6(v-1) | | 41.66=8g+3.58 | | 21x-13=29 | | 2x-12+9x=-56 | | 5z+16=6-5z | | 45x+3=14x+30 | | 3.5(n+5)=30 | | |8x+1|=23 | | 7c-5=6c-9 | | 3/5w-1/3=-1/4 | | (x+25)+(2x+18)=(x2+3) | | 2.6y-6+0.1y=9 | | 3.5(n+5)−8=22 | | 1/4(7x-16)=3 | | x=6+3/8 | | x-6÷3=6 |

Equations solver categories